ANALISIS PENDAPATAN DAN KELAYAKAN USAHA TANI CABAI RAWIT DI DESA TLAGAH KECAMATAN PEGANTENAN KABUPATEN PAMEKASAN - Yanti Nurmalasari; Ruly Awidiyantini (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
Pegantenan is one of the sub-districts located in Pamekasan Regency, Madura where many farmers cultivate tobacco. However, now many farmers have switched commodities by planting cayenne pepper. With the commodity transfer, it is necessary to conduct a study to analyze the income of cayenne pepper farming and the feasibility of farming so that the farmer's decision to switch the commodity is the right decision. This research was conducted to determine the income of cayenne pepper farming and the feasibility of farming cayenne pepper in Tlagah Village, Pegantenan District. This research uses income analysis (π) and feasibility by calculating the R / C ratio and B / C ratio. The results of the analysis show that the average income of cayenne pepper farmers for one planting season is IDR 12.635.000. The result of the R / C ratio analysis is 3.35, where R / C> 1 so that the cayenne pepper farming in Tlagah Village is profitable. The analysis result of B / C ratio is 2.35, where B / C> 0 so that the cayenne pepper farming in Tlagah Village is feasible and provides benefits for farmers.